Effect of Dietary Boswellia serrata Resin on Growth Performance, Blood Biochemistry, and Cecal Microbiota of Growing Rabbits - Ismail, Ismail E.; Abdelnour, Sameh A.; Shehata, Sabry A.; Abd El-Hack, Mohamed E.; El-Edel, Mohamed A.; Taha, Ayman E.; Schiavitto, Michele; Tufarelli, Vincenzo (Frontiers in Veterinary Science, 2019)
The present study aimed to examine the impact of dietary supplementation of Boswellia serrata (BS) (frankincense) resin on growth and carcass traits, blood haematology, serum metabolites and cecal microbiota of growing rabbits. One hundred New Zealand White (NZW) growing male rabbits (6-weeks old) were divided randomly into five groups using different levels of BS (0.00, 0.25, 0.50, 0.75, 1.00 g/kg diet, respectively). When compared to the control diet, daily body weight gain (BWG) and feed conversion ratio (FCR) of rabbits fed BS enriched-diets were improved, while feed intake was significantly decreased. A gradual depression (P < 0.01) in serum triglycerides (TG), total cholesterol (TC) and low density lipoproteins (LDL) were observed with increasing BS level the in diet. Total bacteria count, E. coli and salmonella populations were lower (P< 0.05) in rabbit groups fed diet enriched with BS than that of the control group. Based on these findings, the dietary supplementation of Boswellia serrata enhanced growth, feed efficiency, antioxidant status, and minimize cecal pathogenic bacteria in rabbits.